Breaking the cycle? The effect of education on welfare receipt among children of welfare recipients - Michael B. Coelli; David Alan Green; William P. Warburton (Institute for Fiscal Studies (IFS), 2004)
We examine the impact of high school graduation on the probability individuals from welfare backgrounds use welfare themselves. Our data consists of administrative educational records for grade 12 students in a Canadian province linked with their own and their parents' welfare records. We address potential endogeneity problems by: 1) controlling for ability using past test scores; 2) using an instrument for graduation based on school principal fixed effects; and 3) using a Heckman- Singer type unobserved heterogeneity estimator. Graduation would reduce welfare receipt of dropoutsby Ý to 3/4. Effects are larger for individuals from troubled family backgrounds and low income neighbourhoods.
Keywords: I38; I21; 330; Welfare; Education; Treatment Effects; Bildungsertrag; Kinder; Sozialhilfeempfänger; Kanada; Bildungsabschluss